Effect of Kaempferia galanga L. on in vitro nutrients digestibility, ruminal fermentation and methane production - Kurniawati, Asih; Widodo, Widodo; Artama, Wayan Tunas; Yusiati, Lies Mira (2016)
Kaempferia galanga L. in the diet equal to essential oil level 25 to 100mg/L does not effect on DMD, OMD, CPD, gas production, pH, total VFA, acetate, propionate, butyrate, rumen microbial protein, and ammonia concentration, whereas methane production were lower in fermentation with addition of Kaempferia galanga L. in the diet, and protozoa number increase at dose 50 up to 100mg/L.